Effect of Block Freeze Concentration on Bioactive Compound Content and Antioxidant Capacity When Applied to Peppermint (Mentha Piperita L.) Infusion - Indira Pérez-Bermúdez; Alison Castillo-Suero; Constanza Jara-Leiva; Axel Cortés-Valdivia; Karol Rojas-Rojas; Vivian García-Rojas; Mauricio Opazo-Navarrete; María Guerra-Valle; Guillermo Petzold; Patricio Orellana-Palma (Antioxidants)
This research aimed to evaluate block freeze concentration (BFC) under different centrifugation conditions using response surface methodology to separate an extract from the ice fraction at three centrifugal-BFC (CBFC) cycles, obtaining in the final cycle a phenolic-rich extract. A Box–Behnken design was applied to optimize centrifugation variables, with efficiency of separation (η) selected as the response variable. The extracts were characterized in terms of physicochemical analysis, total and individual bioactive components, and antioxidant capacity. Optimal conditions (3600 rpm, 16 °C, and 14 min) resulted in η of 82%. Thus, from infusion to final cycle, the solids, total polyphenol and flavonoid contents, and antioxidant capacity exhibited from 1.81 to 6.5% (w/w) and 2.5 to 8.7 (°Brix), 0.72 to 12.2 mg gallic acid equivalents/mL, 0.83 to 13.7 mg catequin equivalents /mL, 2.8 to 31.2 μmol trolox equivalents/mL and 4.8 to 122.2 μmol trolox equivalents/mL, identifying by high-performance liquid chromatography that kaempferol, p-hydroxybenzoic, and transferulic acid presented the highest concentrations. The CBFC process has the potential as a non-thermal concentration process to preserve many bioactive compounds, facilitating the production of concentrated fractions with high biological value, where the extracts obtained by BFC are a novel solution for medicinal, pharmaceutical, and food applications.